Câmbio e integração regional: flutuação conjunta e otimização dinâmica para o mercosul - Felipe Motta Benevides Gadelha (2006)
The commercial and economic integration between Brazil and Argentina has been frequently put under risk and uncertainty, so in MERCOSUR, essentially manifested in the tariff compensation. Accounting this concern, one can investigate the importance of exchange in the integration process, the possibility of establishing an harmonic exchange management and its instruments. The Joint Float, used in European Community, was useful as a harmonizing factor of the commercial and macroeconomic relations among members and non-members that informally followed the policy. Besides, the opportune moment of entrance in the coordination is put as extremely important. With this aim put in mind, the right ambience for the joint float, one can launch a dynamic optimization model, with the determination of the best path for the control-variables of monetary policy. For the Robustness of the tools, the time-series modeling was used in the specification of the parameters that work on the control-variable path, overlaying the mathematic model.